1995
DOI: 10.1021/ja00136a028
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Mediated [3 + 2 + 2] Allyl/Alkyne Cycloaddition Reactions. A New Reactivity Pattern for the Synthesis of Seven-Membered Carbocycles

Abstract: The investigation of transition metal-mediated allyllalkyne coupling reactions has revealed a range of synthetically valuable' or potentially e~p l o i t a b l e~.~ reactivity pattems. Particularly interesting are the q3-allyllalkyne cyclization reactions reported by Rubezhov, assembling the q5-cyclopentadieny13a and 7' ,r4-methanocy~lohexadiene~~ ring systems by incorporation of one or two alkyne equivalents, respectively. In this communication, we report a new reactivity pattem on this energy surface: sevenm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…Intermediates similar to D have been suggested for the reactions of [Ir(η 2 -MeC 2 Me)(η 3 -C 3 H 3 )(η 5 -C 5 Me 5 ) + ] with alkynes, in which the coupling of the allyl ligand and two alkyne units led to compounds containing η 5 -cycloheptadienyl ligands …”
Section: Resultsmentioning
confidence: 78%
“…Intermediates similar to D have been suggested for the reactions of [Ir(η 2 -MeC 2 Me)(η 3 -C 3 H 3 )(η 5 -C 5 Me 5 ) + ] with alkynes, in which the coupling of the allyl ligand and two alkyne units led to compounds containing η 5 -cycloheptadienyl ligands …”
Section: Resultsmentioning
confidence: 78%
“…Different researchers have successfully explored functionalized cyclopropanes as 3π components with various alkenes, alkynes, diynes, among others, as 2π components in [3+2+2] cycloaddition reactions using Ni, Pd, Rh and Ru metal complexes as catalysts . The present review summarizes various reports on [3+2+2] cycloaddition reactions with not only products arising from the activity of the key players (different metal complexes) but also those from proton‐based chemistry for the synthesis of mono‐and/or condensed cycloheptadiene derivatives, since 2000.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions gave reasonable yields of 40-78 %; the reaction of 8 with deca-2,8-diyne (9) to give 10 was particularly successful, with a yield of 94 % (Scheme 2). [28] Further investigations with the cheaper catalyst metal cobalt showed that (h 3 -allyl)(h 5 -pentamethylcyclopentadienyl)-cobalt(III) triflates, such as 11, allow the formation of cycloheptatrienyl complexes like 13 by reaction with ethyne (12) or other terminal alkynes, when noncoordinating solvents such as dichloromethane were applied (Scheme 2). The cycloheptadienyl complexes thus obtained can be trapped Scheme 1.…”
mentioning
confidence: 99%